THE INFLUENCE OF COMPUTER ASSISTED LANGUAGE LEARNING ON STUDENTS’ LISTENING SKILLS. - Rizki Nuraida; Hilma Suryani (JR-ELT (Journal of Research in English Language Teaching), 2023)
This study was conducted to determine the influence of computer-assisted language learning on students' listening skills. This research uses descriptive quantitative method in the form of a survey. This method is considered as the right approach for this type of research. Data was collected by distributing it to each class to all twelfth grade in SMAN 4 Batanghari. This study explores students' perceptions that come from students' experiences during the learning process. The results of this study are presented descriptively to reveal students' perceptions comprehensively. This study has a positive influence on computer-assisted language learning by obtaining a Likert scale score which is included in the high category, named 63.70%. it can be concluded that CALL technology can be said to be goood enough to continue to be used in the learning system